Efficient Perovskite Solar Cells Based on Dopant‐Free Spiro‐OMeTAD Processed With Halogen‐Free Green Solvent. Issue 5 (8th March 2019) - Jiang, Kui; Wu, Fei; Zhang, Guangye; Zhu, Linna; Yan, He
Abstract : In this paper, highly efficient (17%) perovskite solar cells (PSCs) based on a hole‐transporting layer (HTL) made of dopant‐free Spiro‐OMeTAD processed from a non‐halogenated solvent (THF) are reported for the first time. In addition to the high efficiency, a negligible hysteresis effect is observed for the devices with dopant‐free Spiro‐OMeTAD hole‐transporting material (HTM), which is often a problem for planar n‐i‐p type PSCs. By eliminating the hydroscopic dopants, the ambient stability of the completed PSC devices are much improved. Another advantage of using THF as a solvent is that much less of the Spiro‐OMeTAD material is required (5 mg ml −1 ) to coat the HTL compared to that used in a conventional chlorobenzene solvent (70 mg ml −1 ). Our result provides a simple yet effective method to fabricate dopant‐free PSCs toward cost‐effective and environmental friendly production of PSCs with enhanced stability. Abstract : A new methodology is presented for preparing a dopant‐free Spiro‐OMeTAD film by dynamic spin‐coating the pristine Spiro‐OMeTAD solution from a halogen‐free green solvent THF, which yields a record efficiency of 17% as along with negligible hysteresis in planar PSCs. Importantly, the strategy brings the field a step closer toward cost‐effective and environmental friendly production of PSCs with enhanced longevity.